Towards the Sustainable Massive Food Services: An Optimization Approach - Vasquez-Perez, O; Espinoza-Perez, A; Garcia-Leal, J (Elsevier Ltd, 2023)
Two important aspects considered by the Sustainable Development Goals are global warming and malnutrition. On the one hand, global warming has had severe negative impacts on the life quality and the efficiency of several productive sectors. On the other hand, malnutrition is a complex issue worldwide, reaching around 60% of the population. In this setting, we conducted a literature review related to diet optimization problems, identifying five research challenges and two main mono-objective and multi-objective problems, providing insights about future work. Consequently, we address the mono-objective problem, introducing the sustainable diets design problem for the massive food services to explore the transformation of the massive food services towards more sustainable consumption patterns. Specifically, we formulate a quadratic mixed-integer programming (QMIP) model to minimize the CO2eq from the system subject to nutritional constraints, operational requirements, and cultural acceptability aspects by considering a bounded budget. Finally, we illustrate the usefulness of our proposal by considering one of the more important public universities in Latin America as a case study. The obtained results allow us to reduce 30.45% the CO2eq and 25.88% of the associated costs. This proposal is easily adaptable to other massive food services institutions such as geriatric services, hospitals, or schools. © 2023 Elsevier Ltd